Maintaining and Maintaining Local Wisdom of Sundanese Culture as One of the Indonesian National Identity - Surya P, Dhika (Communication in Research and Publications (CRP), 2024)
The Sundanese people are part of the people living in Indonesia, the majority of whom are in West Java and its surroundings. Sundanese people have a number of distinctive cultures such as politeness, humility towards others, respect for elders and love for younger people. Spiritual balance is maintained and maintained by carrying out traditional ceremonies, while social balance is by working together to maintain it. However, as time goes by, it is feared that this culture will experience decline and is even vulnerable to extinction. Therefore, in this research, a study was carried out on maintaining and preserving the local wisdom of Sundanese culture, which is part of the identity of the Indonesian nation. The method used is literature study, namely searching various written sources in the form of books, archives, magazines, articles and other relevant scientific works. The results of the study show that in maintaining and maintaining the local wisdom values of the Sundanese people, each individual needs to be aware of how important it is to preserve Sundanese culture so that it does not become extinct. The preservation of this culture, the role of regional beautification and the Indonesian government is also very necessary.